MathsGee is Zero-Rated (You do not need data to access) on: Telkom |Dimension Data | Rain | MWEB

0 like 0 dislike
37 views
Solve the equation:

$5(2-3x)+3(5x-2)-7(4-x)=0$

edited | 37 views

0 like 0 dislike
$5(2-3 x)+3(5 x-2)-7(4-x)=0$
$5(-3 x+2)+3(5 x-2)-7(-x+4)=0$
$(-5 \cdot 3 x+5 \cdot 2)+(3 \cdot 5 x-3 \cdot 2)-(-7 x+7 \cdot 4)=0$
$(-15 x+10)+(15 x-6)-(-7 x+28)=0$
$-15 x+10+15 x-6+7 x-28=0$
$-15 x+15 x+7 x+10-6-28=0$
$7 x-24=0$
$(7 x-24)+24=24$
$7 x-24+24=24$
$7 x=24$
$\frac{7 x}{7}=\frac{24}{7}$
$x=\frac{24}{7}$
by Bronze Status (9,640 points)

0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike